1991
DOI: 10.1016/0014-5793(91)81320-8
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock increases turnover of 90 kDa heat shock protein phosphate groups in HeLa cells

Abstract: I[NTRODUCTIONHeat shock as well as chemical stresses are known to have toxic effects on cellular functions These effects are mostly due to enzymatic inactlvatlon, a consequence of protein denaturatlon caused by cellular stresses [l-3] When cells are allowed to recover by replacing them in normal culture conditions, cellular functions are progressively rescued Recovery 1s probably due, at least partially, to the accumulation, in response to stress, of a specific set of proteins, the heat shock proteins (hsps)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…hsp9O is phosphorylated by casein kinase 11 (7,16,27). Legagneux et al (17) reported the increased turnover of hsp90 phosphate groups in HeLa cells submitted to heat shock, which could be explained by an increased hsp90 phosphatase activity. In vitro experiments to measure the activity of Ptcl against hsp90 and other phosphoproteins using bacterially produced and highly purified Ptcl protein are now feasible.…”
Section: Discussionmentioning
confidence: 99%
“…hsp9O is phosphorylated by casein kinase 11 (7,16,27). Legagneux et al (17) reported the increased turnover of hsp90 phosphate groups in HeLa cells submitted to heat shock, which could be explained by an increased hsp90 phosphatase activity. In vitro experiments to measure the activity of Ptcl against hsp90 and other phosphoproteins using bacterially produced and highly purified Ptcl protein are now feasible.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with a previous study showing rapid dephosphorylation of Hsp90 in heat-shocked HeLa cells. 44 Loss of threonine phosphorylation may impact Hsp90 function in response to heat shock stress or to inhibitory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The Hsp90 phosphorylation level is high under physiological conditions (60). Heat shock conditions induce an increased Hsp90 phosphorylation turnover (61). All known sites reside in the N-domain of Hsp90, but so far, no specific effect can be attributed to a particular phosphorylation event.…”
Section: Post-translational Modificationsmentioning
confidence: 99%